THE EFFECT OF THE NEUROLOGICAL IMPRESS METHOD IN TEACHING READING COMPREHENSION - Ilham, Ilham (Premise: Journal of English Education and Applied Linguistics, 2024)
This study aims to 1) analyse the effectiveness of the Neurological Impress Method in teaching reading at a junior high school in  Lingsar, West Lombok.. This study used a quasi-experimental design with a non-equivalent control group design. The researcher employed two classes in this study, control and experimental classes. This research has 30 students as the sample of study in which each class consists of 15 students. The reading test is utilized for collecting the data as the research instrument. Sampling was carried out using cluster random sampling. The data was analysed using SPSS 12 which the data collected from the pre-test and post-test design. The results showed that the use of the neurological impress method affected students' reading skills. Students' reading achievement before being taught using the neurological impress method in reading texts is generally low, as shown by the average score of 40.76. Students reading achievement after being taught by using the neurological impress method is better than before. This can be seen from the mean value of 67.13. Statistical analysis using paired sample t-test using SPSS 12, indicated by t (0.05) t-table value is (0.000)  and t-value or t-count (0.000). It was lower than the 0.05 level. The alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, this research is expected to provide implications for implementing the neurological impress method for teaching reading skills in junior high schools in Indonesia to encourage the improvement of the neurological impress method on a large scale.